Structure and composition of a mangrove forest on the Central Pacific coast of Costa Rica: population of mollusks of commercial interest - Carvajal-Oses, Milagro (2024)
[Objective]. The floristic composition and populations of associated molluscs of commercial interest of the Chacarita mangrove forest on the Central Pacific of Costa Rica were evaluated to guide proposals for sustainable exploitation activities in the mangrove forest. [Methodology]. Monthly visits to the study area were conducted for one year to establish a floristic baseline of mangrove trees and measure carbon storage. Additionally, bivalve molluscs were collected to analyze the state of their populations based on the abundances of organisms found, as well as other characteristics such as length and mass. Data regarding the mangrove trees included their diameter at breast height (DBH, cm), height (m), importance value index (IVI), and carbon reserves (Mg C·ha-1). Four mollusc species of commercial interest were analyzed, using data on their length (cm), weight (g), and gonadosomatic index. Economic evaluations were also conducted using data obtained from the mangrove forest, as well as tourism and historical fishing data for the collection of Chacarita. [Results]. Five species of mangroves were identified: Rhizophora mangle, Rizophora racemosa, Laguncularia racemosa, Avicennia germinans, and Pelliciera rhizophorae, while P. rhizophorae had the highest importance value index. The study revealed a carbon storage equivalent to 78.49 Mg C·ha-1. A total of 357 organisms were counted, with Anadara similis accounting for 18% of the total count, followed by Anadara tuberculosa (37.5%), Leukoma spp. (41.46%), and Mytella guyanensis (3.08%). When considering the economic value of carbon stocks and the bivalve molluscs obtained from the samples, economic valuations of 9,812.63 USD·ha-1 and 28 USD·ha-1 were determined, respectively. [Conclusions]. The low population densities of molluscs, particularly those belonging to the Anadara genus, necessitate the establishment of management measures to facilitate the recovery of these mollusk populations. This research proposes sustainable use activities such as community tourism for educational and cultural purposes.